Improving diastolic and microvascular function in heart transplantation with donation after circulatory death - Saemann, Lars; Georgevici, Adrian-Iustin; Hoorn, Fabio; Gharpure, Nitin; Veres, Gábor; Korkmaz-İçöz, Sevil; Karck, Matthias; Simm, Andreas; Wenzel, Folker; Szabó, Gábor (International journal of molecular sciences, 2023)
The impact of the machine perfusion of donation after circulatory death (DCD) hearts with the novel Custodiol-N solution on diastolic and coronary microvascular dysfunction is unknown. Porcine DCD-hearts were maintained four hours by perfusion with normothermic blood (DCD-B), hypothermic Custodiol (DCD-C), or Custodiol-N (DCD-CN), followed by one hour of reperfusion with fresh blood, including microvascular and contractile evaluation. In another group (DCD group), one hour of reperfusion, including microvascular and contractile evaluation, was performed without a previous maintenance period (all groups N = 5). We measured diastolic function with a balloon catheter and microvascular perfusion by Laser-Doppler-Technology, resulting in Laser-Doppler-Perfusion (LDP). We performed immunohistochemical staining and gene expression analysis. The developed pressure was improved in DCD-C and DCD-CN. The diastolic pressure decrement (DCD-C: −1093 ± 97 mmHg/s; DCD-CN: −1703 ± 329 mmHg/s; DCD-B: −690 ± 97 mmHg/s; p < 0.05) and relative LDP (DCD-CN: 1.42 ± 0.12; DCD-C: 1.11 ± 0.13; DCD-B: 1.22 ± 0.27) were improved only in DCD-CN. In DCD-CN, the expression of eNOS increased, and ICAM and VCAM decreased. Only in DCD-B compared to DCD, the pathways involved in complement and coagulation cascades, focal adhesion, fluid shear stress, and the IL-6 and IL-17 pathways were upregulated. In conclusion, machine perfusion with Custodiol-N improves diastolic and microvascular function and preserves the microvascular endothelium of porcine DCD-hearts.
Gesehen am 31.10.2023